Surface reconstruction using multiple light sources and perspective projection - Galo, Mauricio [UNESP]; Tozzi, Clesio L. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 1996)
This paper presents a method to recover 3D geometry of Lambertian surfaces by using multiple images taken from the same view point and with the scene illuminated from different positions. This approach differs from Stereo Photometry in that it considers the light source at a finite distance from the object and the perspective projection in image formation. The proposed model allows local solution and recovery of 3D coordinates, in addition to surface orientation. A procedure to calibrate the light sources is also presented. Results of the application of the algorithm to synthetic images are shown.
Keywords: Algorithms; Calibration; Geometry; Image analysis; Light sources; Mathematical models; Three dimensional; Vectors; Video cameras; Lambertian surfaces; Stereo photometry; Synthetic images; Image reconstruction